A Cascaded Multilevel Inverter Using Only One Battery with High-Frequency Link and Low-Rating-Voltage MOSFETs for Motor Drives in Electric Vehicles - Chao Zhang (School of Automation, Beijing Institute of Technology, Beijing 100081, China) (MDPI AG, 2018)
Cascaded H-bridge (CHB) multilevel inverters are widely used in industrial applications, such as medium-voltage conversion and motor drives. However, the DC bus voltage in the electric vehicles is limited and it might not meet the requirements of the inverters for conventional motor drives. This paper presents a solution to drive the conventional motor (3Φ/AC 220 V) with inadequate DC bus voltage (DC 144 V) in an electric vehicle without any extra step-up circuits. The solution consists of a CHB inverter as a motor drive and a high-frequency (HF) transformer to balance the voltage. The multilevel CHB inverter improves the voltage and the current waveforms. High-frequency link (HFL) is used to create several isolated DC sources for the system and it can improve the power density. Besides, it replaces bulky line-transformers in the conventional CHB inverters, and the volume is reduced. Also, the inverter has bidirectional power flow ability, which can improve the efficiency in motor drives. As a result, the reduction of the step-up circuits is achieved and the topology can be used in the electric vehicles that are powered by only one 144 V-battery. The details and the principles of the control algorithm is discussed and an experiment based on a four-level CHB inverter with one DC 30 V power source is carried out to validate the proposed characteristics.